Reformulation of the Criminal Justice System for Children in Conflict Based on Pancasila Justice (Lex Scientia Law Review, 2022)
The writing of this paper aims to examine the policy of the criminal justice system for children in conflict with the law and reformulation of the criminal justice system for children in conflict with the Pancasila justice. The main problem in writing this paper is that why it is considered important to reform the criminal justice system for children in conflict with the law based on Pancasila justice? This study uses secondary data by analyzing the laws of the juvenile justice system in Indonesia and comparing them to the laws and regulations regarding the juvenile justice system in Greece and Yoslavia. The results of the study found that the age requirement for criminal responsibility for children is too low, namely 12 (twelve) years and the terms of diversion, that the threat of criminal acts that can be carried out by diversion and not repetition of criminal acts is not in line with the aim of diversion, namely to prosper and achieve the best interests of children such as recommended by the Convention on the Right of the Child and The Beijing Rules. Therefore, it is important to reformulate/reformulate immediately regarding these diversion requirements. The conclusion of this paper emphasizes the importance of reformulating the criminal justice system for children in conflict with the law (the criminal child) based on Pancasila justice.